KEBIJAKAN PENEGAKAN HUKUM DALAM UPAYA MENANGANI CYBER CRIME YANG DILAKUKAN OLEH POLRI VIRTUAL DI INDONESIA - Mohamad Suarno Nur; Fenty Puluhuwa; Fence M. Wantu (The Juris, 2023)
This research aims to understand and analyze the legal regulatory policies regarding information technology crimes in addressing cybercrime committed by virtual police in Indonesia. In the midst of technological advancements and their negative impacts, especially cybercrimes, handling cybercrime becomes a complex challenge. This study involves normative legal analysis focusing on doctrines and legal principles found in legislation and court decisions.The results indicate that the criminal legal regulations related to cybercrime in Indonesia are not yet fully adequate. Although Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions has regulated some aspects, further harmonization and adjustment are still needed in line with the development of cybercrimes. In dealing with cybercrime, the roles of virtual police and cyber police in Indonesia need to be clearly understood. Virtual police emphasize preventive efforts, while cyber police follow up on cases through law enforcement. The existence of this difference needs to be socialized so that the public understands their roles in combating cybercrime.